Mapping Fish Chorus Distributions in Southern California Using an Autonomous Wave Glider - Pagniello, Camille M. L. S.; Cimino, Megan A.; Terrill, Eric (Frontiers in Marine Science, 2019)
Passive acoustics is a tool to monitor behavior, distributions, and biomass of marine invertebrates, fish, and mammals. Typically, fixed passive acoustic monitoring platforms are deployed, using a priori knowledge of the location of the target vocal species. Here, we demonstrate the ability to conduct coastal surveys of fish choruses, spatially mapping their distributions with an autonomous surface vehicle. For this study, we used an autonomous Liquid Robotics Wave Glider SV3 equipped with a Remora-ST underwater acoustic recorder and hydrophone. The exploratory 15-day deployment transited through three marine reserves, resulting in approx. 200 hours of passive acoustic recordings, and revealed five distinct fish choruses from La Jolla to Capistrano Beach, CA (approx. 80 km separation), each with unique acoustic signatures. Choruses occurred in the evening hours, typically in the 40 to 1000 Hz band. There was a lack of both temporal and frequency partitioning amongst the choruses, but some choruses exhibited distinct spatial niches by latitude and water temperature. These results suggest that the mobility of the Wave Glider allows for persistent surveys and studies that otherwise may be too challenging or costly for stationary or ship-based sensors; a critical consideration for documenting biological activity over large spatiotemporal scales, or sampling of nearshore marine reserves.